Maritime Safety and Security Policies to Support Marine Transportation Systems - Febriansyah Febriansyah; Maghdalena Febriani; Elfita Agustini (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2020)
All users of sea transportation in Indonesia in particular and in the world in general, always prioritize safety and security issues, which are then followed by aspects of affordable costs, speed and timeliness, and aspects of comfort.The occurrence of ship accidents such as drowning, burning, etc. are issues related to the safety and security of marine transportation. For the implementation of this sailing safety improvement, the Directorate General of Sea Transportation has issued policies in the prevention of ship accidents such as making shipping announcements about improving shipping safety supervision for passenger ships, making announcements about marine weather conditions in Indonesia such as telegrams regarding bad weather readiness at sea.This study aims to analyze maritime safety and security policies in supporting the marine transportation system. This study used a descriptive method, because the data were collected in the form of words, pictures, and not numbers. The data comes from interview scripts, field observations/notes, Focus Group Discussion, videotapes, photos, notes or memos, and other official documents. Data analysis using ethical and emic approaches and triangulation processes. Determination of informants using purposive technique. Research results: Sea transportation in Indonesia has not been optimally developed, but has a strong potential to be developed, given its characteristics that are capable of mass transportation. Therefore, the safety and security system is a key factor that must be considered and as a basis and benchmark for decision makers.Government policies in the maritime sector, both the fishing industry and the shipping industry have not been implemented consistently in accordance with the applicable law. So far, the development of maritime potential has been hit by structural problems, and there has been no national political awareness of how great this economic, fishery and maritime potential is. Mas little is known about the potential content of Indonesia's marine resources, thus opening the door for various researches and development of such biodiversity.